MOLECULAR DETECTION AND PHYLOGENETIC ANALYSIS OF FASCIOLA GIGANTICA ISOLATED FROM BUFFALOES AT AL-MUTHANNA PROVINCE, IRAQ - H. J. Jasim,; A. M. Al-Amery, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The aim of this study was to identify and differentiate between Fasciola gigamtica and Fasciola hepatica infections in buffaloes, through the application of PCR technique. Also, includes investigate the characteristics of phylogenetic analysis for Fasciola gigantica based on partial mitochondrial DNA. The application of polymerase chain reaction technique (PCR) in molecular diagnosis was exhibited high levels of specificity and sensitivity in identifying both species of Fasciola depend on two different genes NADH 6 for F. hepatica and NADH 4 for F. gigantica. Moreover the percentage of infection by F. hepatica and F. gigantica were recorded using specific different primers to be 0% and 100 % respectively. The results of the sequencing and phylogenetic tree showed 99% identification with three China isolate (MH621335.1, GU121036.1, GU121037.1), and 98% identification one China isolate. Furthermore, the results showed 100% identification with two Niger isolate (GU121056.1, GU121048.1), and 99% identification with two Niger isolate (GU121047.1, FJ392263.1) based on sequence analysis of mitochondrial NADH 4 gene (ND4). Thus, the current study concluded that the phylogenetic analysis exhibited a significant genetic resemblance between the strains from Iraq and Niger.